What determines attitudes to immigration in European countries? An analysis at the regional level - Yvonni Markaki; Simonetta Longhi (University of Essex, Institute for Social and Economic Research (ISER), 2012)
Different disciplines within the social sciences have produced large theoretical and empirical literatures to explain the determinants of anti-immigration attitudes. We bring together these literatures in a unified framework and identify testable hypotheses on what characteristics of the individual and of the local environment are likely to have an impact on anti-immigration attitudes. Most of the previous literature focuses on the explanation of attitudes at the individual level. When cross country comparisons are involved the heterogeneity across countries is modelled by fixed or random effects in multilevel models. We analyse anti-immigration attitudes across regions of 24 European countries to explain why people living in different regions differ in terms of their attitudes towards immigration. We isolate the impact of the region from regressions using individual-level data and explain this residual regional heterogeneity in attitudes with aggregate level indicators of regional characteristics. We find that regions with a higher percentage of immigrants born outside the EU and a higher unemployment rate among the immigrant population show a higher probability that natives express negative attitudes to immigration. Regions with a higher unemployment rate among natives however, show less pronounced anti-immigrant attitudes.
Keywords: F22; J15; J61; R19; 330; anti-immigration attitudes; regional characteristics; Europe